Analisis Efektivitas Transformasi Digital dalam Skema Sertifikat Halal di Provinsi Banten - Rita Sari Puspita; Mari Maryati; Eddy Soeryanto Soegoto; Rahma Wahdiniwaty; Irfan Dwiguna Sumitra; Adam Mukharil Bachtiar; Suryatno Wiganepdo Soegoto (JEMBA, 2026)
Digital transformation has become a central element of public service reform, including the implementation of halal certification in Indonesia. This study aims to analyze the effectiveness of digital transformation in the halal certification scheme in Banten Province and to identify the key factors influencing its performance. A quantitative explanatory approach was employed through a survey of 235 micro and small enterprise owners who had applied for or were in the process of applying for halal certification using a digital system. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that digital transformation has improved service accessibility and transparency; however, its overall effectiveness has not yet been fully achieved, particularly in terms of process efficiency and time certainty. The effectiveness of digital halal certification services is influenced by system quality, information quality, quality of facilitation services, and users’ facilitating conditions. These results suggest that the success of digital transformation in regulatory public services is not determined solely by technological quality, but also by implementation support and contextual factors at the regional level. Theoretically, this study contributes to the literature on digital transformation in the public sector by emphasizing a public value and socio-technical perspective in evaluating service effectiveness. Practically, the findings provide insights for improving the governance of digital halal certification through strengthening facilitation mechanisms, enhancing digital literacy among enterprises, and adopting more context-sensitive implementation strategies.